Case Report: Megasystis Janin pada Kehamilan Gemelli Terkait Kelainan Kongenital dan Outcome Obstetri - Agoeng Basoeki, Rijanto; Annisya, Emmy Indri (JurnalMU: Jurnal Medis Umum, 2025)
Background: Megacystis is a congenital lower urinary tract obstruction (CLUTO) disorder diagnosed via ultrasound, with bladder enlargement detectable from 10 weeks of gestation. Although easily identified through imaging, its management is complex due to varying etiologies. This condition can impact fetal development, necessitating further understanding. Objective: This case report describes the diagnosis of fetal megacystis in a twin pregnancy. Case Presentation: A 27-year-old woman at 8 months of gestation presented to Fatimah Hospital, Lamongan, with abdominal tightness and vaginal bleeding. Obstetric examination revealed a twin pregnancy at 33 weeks, with Fetus I in an oblique lie, low-lying placenta, and sufficient amniotic fluid, while Fetus II was in a cephalic position with suspected intrauterine fetal death (IUFD). Ultrasound confirmed megacystis in Fetus I, leading to an emergency cesarean section. Baby I was born weighing 2100 grams with Apgar scores of 5-6, while Baby II, diagnosed with fetal megacystis, was stillborn at 500 grams. Conclusion: Megacystis, defined as bladder enlargement >7 mm between 1-18 weeks of gestation, poses significant risks to fetal development. Its prognosis depends on bladder size and underlying causes. Twin pregnancies have a higher incidence of congenital abnormalities due to embryogenesis failure. Delivery mode should consider fetal position, heart rate monitoring, and maternal-fetal status.